Normal sonographic liver and spleen dimensions in a central European pediatric population - Stephan Waelti; Tim Fischer; Simon Wildermuth; Sebastian Leschka; Tobias Dietrich; Sabine Guesewell; Pascal Mueller; Michael Ditchfield; Stefan Markart (BMC, 2021)
Abstract Background Organ size is influenced by a number of factors. Age, height, weight, and ethnicity are known influencing factors. Pediatric populations have changed over time, puberty beginning earlier resulting in a changing growth pattern of their organs. Hence, contemporary charts using local data are considered the most appropriate for a given population. Sonographic charts for liver size for a predominantly Caucasian population are limited, which has implications for clinical practice. The aim of this study was to define a contemporary normative range of liver and spleen sizes for a healthy, predominantly Caucasian population and for all pediatric age groups (0-18 years) and to investigate whether there is a size difference between genders and ethnicities. Methods Retrospective study including children with normal sonographic findings and no evidence of liver or splenic disease clinically. Craniocaudal and anteroposterior dimensions are measured for the right and left lobe of the liver, and craniocaudal dimension for the spleen. Relationship of the liver and spleen dimensions with age, body length, body surface area, weight, and gender were investigated. Charts of normal values were established. Values were compared to studies involving other ethnicities and to one study carried out in 1983 involving the same ethnicity. Results Seven hundred thirty-six children (371 boys, 365 girls) aged 1 day - 18.4 years were included. From the second year of life, the craniocaudal dimension of the right lobe of the liver is 1-2 cm larger in the Central European population compared with non-Caucasian populations at a given age. Liver size of Central European children in 2020 is greater compared to a similar population almost 40 years ago. The craniocaudal dimension of the spleen of Central European, US-American and Turkish children is similar. The difference between genders is statistically significant for both the liver and the spleen, being larger in boys. Conclusion Contemporary and ethnically appropriate reference charts for liver and spleen measurements should be used, especially for liver size. The effect of ethnicity is reduced if patient height rather than age is referenced.